2021
DOI: 10.2174/1871526520666200622142710
|View full text |Cite
|
Sign up to set email alerts
|

Miracles of Herbal Phytomedicines in Treatment of Skin Disorders: Natural Healthcare Perspective

Abstract: Human skin considered as the first line of defense and barrier against the majority of infections caused through the skin that are affecting human populations. Healthy skin, promotes healthy body that can achieve with the usage of modern, allopathic and natural remedies. Major skin ailments affecting human populations are skin cancers, eczema, herpes infection, fungal infection, anti-aging, itching, insect bites, pemphigus vulgaris, trauma, psoriasis, athlete’s foot infections, rashes, skin pigmentation, acne,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Poultice had become an effective way to treat skin diseases, 116 injuries, 117 and pain 118 in many countries around the world. 119 , 120 It can act on the local drug more directly to solve the local problem.…”
Section: Resultsmentioning
confidence: 99%
“…Poultice had become an effective way to treat skin diseases, 116 injuries, 117 and pain 118 in many countries around the world. 119 , 120 It can act on the local drug more directly to solve the local problem.…”
Section: Resultsmentioning
confidence: 99%
“…These plants act as antiaging and antioxidant factors, improve cognitive impairments, reduce oxidative stress and other age associated markers, and reduce cardiovascular and neurodegenerative risks, through physiological and molecular mechanisms. Different bioactive compounds in these plants makes it multi-faceted with limited or negligible side effects, making it one of the most preferred medication [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study showed the minimal erythema dose had been increased while sunburn cells and melanin levels were reduced after oral administration of a specific melon concentrate rich in superoxide dismutase [9]. Apart from effective functions, there has been a lot of scientific reports that demonstrated the safety and good tolerance of those natural ingredients, which is also among the first priorities for individuals for the consideration of a specific cosmetic product [10].…”
Section: It Has Been Demonstrated Utilizations Of Certain Naturalmentioning
confidence: 99%